Analysis of glucose and amino acid combination for Cherax quadricarinatus growth and characteristics - Nurul Mutmainnah; Lidya Lidya; Zulfiani Zulfiani; Fitri Indah Yani; Mayasari Yamin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Freshwater crayfish (Cherax quadricarinatus) is a valuable aquaculture commodity with relatively easy cultivation. However, low larval survival during early developmental stages remains a major challenge in its farming. This study aims to evaluate the effects of dissolved glucose and amino acid combinations on growth characteristics, molting frequency, and survival rate. The research was conducted in the Greenhouse of the Faculty of Agriculture, Animal Husbandry, and Fisheries, Universitas Muhammadiyah Parepare, using hatchery-produced crayfish larvae. Four dosage combinations were tested: A) 100 ppm glucose + 250 ppm amino acids, B) 150 ppm glucose + 200 ppm amino acids, C) 200 ppm glucose + 150 ppm amino acids, and D) 250 ppm glucose + 100 ppm amino acids, each replicated three times. The results showed that glucose and amino acid combinations significantly affected crayfish length growth. The highest absolute length growth was observed in the 250 ppm glucose + 100 ppm amino acid group. Meanwhile, the 150 ppm glucose + 200 ppm amino acid combination showed the best performance in molting frequency, number of molting crayfish, survival rate, and percentage of surviving crayfish. The optimal treatment for supporting freshwater crayfish growth and development was the 150 ppm glucose + 200 ppm amino acid combination.Keywords:Cherax quadricarinatusGlucoseamino acidsgrowth characteristicssurvival ratemolting